Development of a Mobile Application Enhancing Students’ Ability to Serve as Volleyball Referees - Gingsomklang, Jakgrawat; Wanichsan, Dechawut; Pitanon, Konggrit (ARU Research Journal Humanities and Social Sciences, 2026)
The objectives of this research were: 1) to develop a mobile application for learning volleyball referee hand signals; and 2) to examine the learning achievement of students using the application. The sample consisted of 100 physical education students from the Faculty of Education, selected through simple random sampling (draw method) and divided into an experimental group (n = 50) and a control group (n = 50). The research instruments included the mobile application on volleyball referee hand signals and a learning achievement test. Data were analyzed using mean, standard deviation, and t-test for independent samples. The findings revealed that: 1) the development of the mobile application was highly appropriate (Mean = 4.77, SD = 0.14), and the achievement test demonstrated a high level of reliability with a Cronbach’s alpha coefficient of .89; and 2) the learning achievement scores of students who used the application were significantly higher in the post-test than in the pre-test at a .05 level of significance, with an average pre-test score of 9.98 (SD = 3.87) and an average post-test score of 13.28 (SD = 4.10).